Validity and Practicality Meta-analysis: Teaching Modules Nuanced by the Pancasila Student Profile in Implementing Merdeka Curriculum - Lufri; Safira Hayyu Fauzia (Jurnal Profesi Keguruan, 2024)
Education helps shape the positive perception of society so that it can reach its maximum potential. Article 3 of Law No. 20 of 2003 concerning the Education System states that students can develop into complete and dignified human beings. To develop noble morals, students must apply the Pancasila values contained in the Pancasila Student Profile in the Independent Curriculum. The Merdeka curriculum places great emphasis on allowing instructors to create their own courses. A meta-analysis is an examination of multiple research findings on related issues as part of a larger study. The purpose of this meta-analysis study is to evaluate the degree of validity and applicability of each data collected. Based on the results of an analysis conducted on 10 articles, the Nuanced Module of the Pancasila Student Profile is very appropriate to be used and developed in the classroom with 91.87% validity results and 82.56% practicality results. Thus, the Nuanced Teaching Module of the Pancasila Student Profile in the application of the Independent Curriculum can be used in learning in schools